2014
DOI: 10.1021/nl502074d
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Helium Implantation on the Tensile Properties and Microstructure of Ni73P27 Metallic Glass Nanostructures

Abstract: We report fabrication and nanomechanical tension experiments on as-fabricated and helium-implanted ∼130 nm diameter Ni 73 P 27 metallic glass nanocylinders. The nanocylinders were fabricated by a templated electroplating process and implanted with He + at energies of 50, 100, 150, and 200 keV to create a uniform helium concentration of ∼3 atom % throughout the nanocylinders. Transmission electron microscopy imaging and through-focus analysis reveal that the specimens contained ∼2 nm helium bubbles distributed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
36
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(38 citation statements)
references
References 65 publications
(99 reference statements)
1
36
0
Order By: Relevance
“…Furthermore, through controlled surface ion-implantation, it was also demonstrated that nano-scale plasticity of MGs can be tuned by adjusting the dose of the implanted ions2223. In view of these recent findings20212223, one can conclude that the behavior of nano-scale shear-banding in MGs relies on how micro-samples are prepared. Hence, the issue of size effect on shear-banding in pristine MGs is not completely settled and more research efforts are still needed.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…Furthermore, through controlled surface ion-implantation, it was also demonstrated that nano-scale plasticity of MGs can be tuned by adjusting the dose of the implanted ions2223. In view of these recent findings20212223, one can conclude that the behavior of nano-scale shear-banding in MGs relies on how micro-samples are prepared. Hence, the issue of size effect on shear-banding in pristine MGs is not completely settled and more research efforts are still needed.…”
mentioning
confidence: 96%
“…Compared to the micro- and nano-compression techniques, indentation does not entail a complicated process for preparing small-sized samples, such as the use of focused ion beam (FIB) to fabricate micro-/nano-pillars for testing, during which process surface defects might be introduced, thus altering the mechanical behaviors of the micro-samples so obtained202122. This is particularly so for MGs as noted in a few recent studies2122. According to Magagnosc et al 21,.…”
mentioning
confidence: 99%
“…The central premise is that certain types of defect sinks may promote the absorption and recombination of interstitials and vacancies and thus enhance the radiation tolerance of materials. Consequently, various types of defect sinks have been investigated, including grain boundary (GB), twin boundary (TB), phase boundary, etc101112131415161718. Nanocrystalline materials have abundant GBs and may have extraordinary radiation resistance because GBs act as defect sinks that can absorb irradiation induced defects, and in some cases may serve as sources to emit interstitials and annihilate vacancies1920212223.…”
mentioning
confidence: 99%
“…[19][20][21][22][23][24][25] Generally these microstructures consist in few pores situated at a certain distance from the surface; while with our methodology, highly porous structures with uniform porosity from the substrate to the coatings surface are deposited, in a wide range of thicknesses (from 100 nm to few microns). From a fundamental point of view these new materials with embedded pores, filled with the sputtering gas, represent a new class of nanocomposite materials presenting on demand optical properties in comparison with the matrix film.…”
mentioning
confidence: 99%